2002
DOI: 10.1074/jbc.m107128200
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between AMP-activated Protein Kinase Activity and AMP Concentration in the Isolated Perfused Rat Heart

Abstract: AMP-activated protein kinase (AMPK)1 and AMPK kinase comprise a protein kinase cascade that has been highly conserved throughout evolution (1, 2). Increases in AMP concentration ([AMP]) activate this cascade by four mechanisms (3-5). These mechanisms are as follows: 1) an allosteric activation by AMP of AMPK kinase, which then phosphorylates AMPK; 2) the binding of AMP to AMPK, which makes it a poorer substrate for protein phosphatases; 3) the binding of AMP to AMPK, which makes AMPK a better substrate for AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 33 publications
4
63
0
Order By: Relevance
“…The associated model predictions are coincident with several experimentally observed phenomena: (i) the predicted metabolic tipping point coincides with the transition to severe cardiac dysfunction indicated by end-diastolic pressures greater than 15 mmHg in dogs (6,8); (ii) the tipping point is associated with a Ϸ30% reduction of TAN reduction (Fig. 2D), consistent with observations in humans in heart failure (3); (iii) the predicted cytoplasmic AMP at the tipping point is Ϸ1.6 mM and equal to the apparent AMP concentration at half-maximal activation of cardiac AMP-activated protein kinase (17); (iv) oxidative stress in the myocardium is predicted to progressively increase as the metabolic pools are diminished; and (v) at given values of TAN and TEP during hypertrophic remodeling, CR tot attains a value that is associated with optimal ⌬G ATPase . Thus, both increases and decreases to the creatine pool are predicted to result in diminished energetic state unless accompanied by appropriate simultaneous changes in the other pools.…”
Section: Resultssupporting
confidence: 71%
“…The associated model predictions are coincident with several experimentally observed phenomena: (i) the predicted metabolic tipping point coincides with the transition to severe cardiac dysfunction indicated by end-diastolic pressures greater than 15 mmHg in dogs (6,8); (ii) the tipping point is associated with a Ϸ30% reduction of TAN reduction (Fig. 2D), consistent with observations in humans in heart failure (3); (iii) the predicted cytoplasmic AMP at the tipping point is Ϸ1.6 mM and equal to the apparent AMP concentration at half-maximal activation of cardiac AMP-activated protein kinase (17); (iv) oxidative stress in the myocardium is predicted to progressively increase as the metabolic pools are diminished; and (v) at given values of TAN and TEP during hypertrophic remodeling, CR tot attains a value that is associated with optimal ⌬G ATPase . Thus, both increases and decreases to the creatine pool are predicted to result in diminished energetic state unless accompanied by appropriate simultaneous changes in the other pools.…”
Section: Resultssupporting
confidence: 71%
“…The rapid increase in glycogenolysis in G-replete hearts provides more than 85% of glucose consumed through glycolysis during the initial 10 min of LFI, and the elevation of glucose-6-phosphate availability suppresses hexokinase activity (22) and thereby slows the rate of glucose uptake. Similar observations were reported for skeletal muscles during moderate exercise (20). Because of the finite supply of glycogen, glycogenolysis slows during more prolonged periods of LFI, and, consequently, glucose uptake recovers to maintain substrate availability for glycolysis.…”
Section: Discussionsupporting
confidence: 70%
“…AMPK is a key kinase involved in the regulation of many aspects of cellular metabolism, including glucose metabolism (20,29,30,51). AMPK activation by AICAR in rat skeletal muscles is accompanied by an activation of glycogen phosphorylase that increases glycogenolysis (51), but no such relationship occurs in rat ventricular papillary muscle (38).…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the role of AMP in the control of AMPK has been hampered by the complexity of accurately measuring cytoplasmic [AMP], as total cellular AMP content does not reflect cytoplasmic [AMP]. However, studies by Frederich et al 25 have carefully examined the relationship between AMPK and AMP, using a 31 P-NMR approach in which cytoplasmic [AMP] concentrations can be calculated. These authors showed that cardiac AMPK is activated by AMP concentrations in the low micromolar range.…”
Section: Ampk Activation During Ischemia/reperfusionmentioning
confidence: 99%